NEGOSIASI DALAM HUKUM ISLAM: - Fauziah, Umi Fajar; MUSONNIF, AHMAD (UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Fitrah Zakat plays a central role as an obligatory duty that cannot be ignored. Fitrah zakat is a mandatory contribution for every individual in the Muslim community, known as (zakat al-nafs). It must be distributed accurately to those entitled (mustahiq), ensuring the goal of meeting the needs of the mustahiq during festive occasions is achieved. This research is motivated by the zakat distribution practices in Pojok Village, where several hamlets distribute zakat evenly among the local community. The study critically examines the concept of negotiating zakat distribution within Islamic law, particularly through the principle of